Correlation Between Psoriasis Severity and Dyslipidaemia in Iraqi Patients - Jasim, Samar Ahmed; Abbas, Mohammed; Mustafa, Ethar Thaer; Khalid Abdulqader, Shaymaa (Scripta Medica, 2025)
Background/Aim: Psoriasis is a persistent systemic disorder characterised by chronic inflammation and linked to multiple comorbidities, including arthritis, cardiometabolic disorders, obesity and hyperlipidaemia. Objective of this study was to identify the relationship of abnormal lipid profiles and psoriasis, as well as to pinpoint factors that correlate with disease severity. Patients and methods: A cross-sectional study was carried out at the dermatology clinic over 6 months from the 1 August 2024 to the 1 February 2025. Patients aged 15 years and above with a diagnosis of psoriasis were enrolled. For each patient two sets of data were collected, demographical characteristics (age, sex, disease duration and the body mass index (BMI)) and the lipid profile (total cholesterol (TC), total triglyceride (TG), low-density lipoprotein (LDL) and high-density lipoprotein (HDL)). The psoriasis severity determined by the Psoriasis Area and Severity Index (PASI) and accordingly, the association between patients' BMI and lipid profile with PASI score were assessed.Results: A total of 93 psoriasis patients were recruited over the study period. The mean of the patients age was 45.49 ± 10.71 years with about two-thirds of them being females. Severe psoriasis where significantly correlated with BMI and elevated serum levels of TG and TC, LDL and low levels of HDL, p < 0.001. PASI score had a positive significant correlation with each of BMI (p < 0.001), disease duration (p = 0.046), TC (p < 0.001), TG (p < 0.001) and LDL-C (p = 0.003). On the other hand, the PASI score displayed a significant negative correlation with HDL-C (p < 0.001)Conclusion: A significant association between psoriasis severity and metabolic disturbances, including dyslipidaemia and overweight was found in Iraqi adults with psoriasis.
Keywords: Body mass index; Lipoproteins, HDL; Triglycerides; Psoriasis; PASI